Analysis of Soil Erodibility Value Using the Wischmeier-Smith Method - Marchelino Rendi Pradana; Purnomo Edi Sasongko; Maroeto Maroeto (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Soil erodibility is an important factor in determining soil loss. The objective of this study was to evaluate the soil erodibility value based on the Wischmeier-Smith Method. The study was carried out in Jatiarjo Village, Prigen District, Pasuruan Regency, at four land use units (LUU), including Mounts (MO), Mixed Garden (MI), Monoculture Garden (MG), and Shrubs (SR). Wischmeier-Smith algorithm was used to determine the erodibility values and classification. Results showed that shrub was identified as the land use with the highest potential for erosion and erodibility value. The correlation between clay fraction and erodibility has a negative value wit r = -0.76, while other fractions had r value < 0.5. This implied that the clay fraction and soil erodibility have an inverse relationship, where each increase in the clay fraction value will be followed by a decrease in the erodibility value. One way to reduce soil erodibility is to increase plant diversity on the land. Apart from adding organic matter, a variety of plants also have roots that are able to bind soil aggregates and help absorb water into the soil, thereby reducing water flow on the surface. If conservation is not taken seriously, it can undoubtedly result in.